Answer:
x = -3 and x = -3/2
Step-by-step explanation:
After writing down the polynomial, split it; put a line between 3x^2 and -18x. Look and 2x^3 + 3x^2 and -18x - 27 separately and factor them both:
p(x) = 2x^3 + 3x^2 <u>- 18x -27</u>
p(x) = x^2(2x+3) <u>-9(2x+3)</u>
Now notice how x^2 and -9 have the same factor (2x+3). That means x^2 and -9 can go together:
p(x) = (x^2 - 9)(2x+3)
Factor it once more because there's a difference of squares:
p(x) = (x+3)(x-3)(2x+3)
Now just plug in whatever makes the each bracket equal 0:
x = -3, x = 3, and x = -3/2
Those are your zeros.
Answer:
4387 x 9 = 39,483
Step-by-step explanation:
Please consider giving me Brainliest
darrylh3333
Hope this helps
:)
Answer:
$40
Step-by-step explanation:
If he spent $40 and has none left that means he currently has $0.
If you subtract $40 - b = $0
b = $40
Answer:
Step-by-step explanation:
First, we find the greatest common factor 50, 10 and 2.
It is 2.
Then, we find the greatest common factor of and which is .
Thus, the greatest common factor is